Shear Bond Strength of Dental Cements on Titanium Alloy: Use of Different Restorative Materials (Majalah Kedokteran Bandung, 2022)
Different dental cements and restorative materials may have various impacts on the shear bond strength (SBS) to titanium alloy of dental implants, and some fluoride-containing cements may destroy the oxide layer of Ti alloys. The aim of this study was to evaluate the retention and SBS of different dental cements to titanium alloy using different restorative materials and also the corrosive effect of dental cements on titanium alloy. In this in-vitro study, a total of ninety titanium alloy discs (10×3 mm) and restorative material discs (7×3mm) consisting of Co-Cr soft metal, zirconia, and Ni-Cr were constructed. Three dental cement of 2 different compositional classes, glass ionomer (GI) and zinc phosphate (ZP), were used to cement the discs (n=10 in each paired disks). SBS was evaluated using a universal testing machine with a cross-head speed of 1mm/min. A stereomicroscope (×32) and a scanning electron microscope were used to determine the fracture pattern and titanium corrosion, respectively. Data were then analyzed statistically using one-way ANOVA and Tamhane comparison test (P
Keywords: Bond strength; corrosion; lutting cement; titanium alloy